Safety Assessment of Combination of Tinospora crispa Extract, Andrographis paniculata, Cinnamomum burmanii, Syzygium polyanthum and Momordica charantia in Hepar and Renal Function - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Tinospora crispa, Andrographis paniculata, Cinamomum burmanii, Syzygium polyanthum and Momordica charantia contain phenolics and flavonoids which are rich in benefits. Phenolic compounds are compounds that have an aromatic ring with one or more hydroxy groups, compounds derived from plants that have the same characteristics, namely aromatic rings containing one or more hydroxyl groups. Herbal plants, which are rich in phenolic compounds, have the efficacy, among others, as antioxidants, anti- inflammatory, antimicrobial, anti-fungal and prevents tumor growth. The acute toxicity test is a procedure designed to determine the median lethal dose of a substance and its possible mechanism of action and target organs. In simple terms, toxicity can be defined as the ability of a compound that can cause harmful effects or deviate from the biological mechanism in an organism.